NILAI-NILAI KARAKTER DALAM FILM ANIMASI THE GOOD DINOSAUR DAN RELEVANSINYATERHADAP PERKEMBANGAN ANAK USIA DINI - Husnul hafidhoh Husnul; Raden Rachmy Diana (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2021)
The Values of the nation's character must be preserved so as not become extinct. Technological advances at this time can affect people's behavior. Seeing the current phenomenon, there are many moral or moral crises, such as corruption, illegal racing, environmental damage, and so on. Children are the next generation of the nation, for that it is important to instill noble values from an early age. As adult figures we can model good behavior. Children have an easy nature to imitate, it will be more useful it what children see and hear is something positive. Research on character values in the animated film The Good Dinosaur and its relevance to early childhood development. This study aims to determine the values of the characters in the animated film The Good Dinosaur and their relevance to early chilhood development. The method used in this study is library research using a structuralism approach, because this study examines the overall structure of the fil starting from the shot, scene, sequence and dialogue between characters and produces the necessary data. in this study are presented in the from of a narrative. The result found in the animated fil the Good Dinosaur can affect a child's development in the animated film The Good Dinosaur, seven character values are found, namely the value of social care, the value of hard work, the value of creative, friendly/communicative values, the value are in accordance with Erikson's social theory.